2011
DOI: 10.1007/s11751-011-0114-3
|View full text |Cite
|
Sign up to set email alerts
|

Controversial topics in the management of displaced supracondylar humerus fractures in children

Abstract: The aim of our study was to review the literature looking for the up to date information regarding these controversial topics. An electronic literature search was performed using the Medline/PubMed database. A closed reduction attempt should always be done first. It is more important to engage both columns as well as divergence of the pins no matter whatever configuration is applied. Time to surgery seems to be not an important factor to increase the risk of complications as well as open reduction rate. Usuall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 44 publications
0
14
0
Order By: Relevance
“…[13,14] Some authors assert the importance of an additional medial K-wire to prevent reduction loss. [15,16] Incidence of iatrogenic nerve injury of 14.3% was recently reported in surgically treated cases of supracondylar humerus fracture. In the same study, the ulnar nerve was reported as that most commonly injured (82.1%), followed by the radial (7.7%) and median (5.1%) nerves.…”
Section: Introductionmentioning
confidence: 99%
“…[13,14] Some authors assert the importance of an additional medial K-wire to prevent reduction loss. [15,16] Incidence of iatrogenic nerve injury of 14.3% was recently reported in surgically treated cases of supracondylar humerus fracture. In the same study, the ulnar nerve was reported as that most commonly injured (82.1%), followed by the radial (7.7%) and median (5.1%) nerves.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, incidence peaks between the ages of 5-7 have been reported. 12,14,15 Supracondylar fractures of humerus are common in boys compared to girls. In our series, 72% were boys and 28% were girls.…”
Section: Discussionmentioning
confidence: 99%
“…If the ulnar nerve cannot be located, the use of a small incision (Gordon et al, 2001;Gosens & Bongers, 2003;Green et al, 2005;Zaltz et al, 1996) or nerve-stimulation is advised (Michael & Stanislas, 1996). Even if a nerve gets iatrogenically damaged, it usually recovers spontaneously within a certain time (Culp et al, 1990;D'Ambrosia, 1972;Dodge, 1972;Fowles & Kassab, 1974;Ikram, Joist et al, 1999;Lyons et al, 1998;Pretell-Mazzini et al, 2011;Rasool, 1998;Royce et al, 1991;van Vugt et al, 1988).…”
Section: Discussionmentioning
confidence: 99%